(untitled) (Innovaciones Educativas, 2023)
Universities have a crucial responsibility in their role of social and professional training, as well as being vehicles of social mobility in the current difficult global socioeconomic context. For this reason, it is especially relevant not only to have psychometrically adequate instruments, but also easy to apply with respect to the quality of education. The aim of this article is to explore the psychometric properties of an academic satisfaction (AS) instrument developed from the self-evaluation questionnaire of the National Higher Education Accreditation System (SINAES), used by universities seeking accreditation in Costa Rica, together with the relevant information found in this particular case. The instrument was applied to 226 students of Medical Sciences at UNIBE in person during the first four-month period of the year 2021 in San José. As a result, after an exploratory factor analysis, the DESIT-17 was obtained, an instrument to measure SA based on four factors of satisfaction: with the teaching attention (SAD), with the equipment (SAE), with the services (SAS), and with the scientific and technological aspects of the training (SACT). In addition, it was found that the more time elapsed since entering the career, the lower the level of both general SA and its factors, while age shows no relationship with SA, except for SAS, which is lower in older students. Finally, a lower SAE was found in 16.9% of students who report working.